REVIEW OF JUDICIAL PRACTICE ON THE CONDUCT OF COVERT INVESTIGATIVE (SEARCH) ACTIONS (Bulletin of criminological association of Ukraine, 2024)
It has been emphasized that secret investigative (search) actions in accordance with criminal procedural legislation are means of proof in criminal proceedings, which are carried out by an appropriate subject, on the grounds and in the manner determined by the Code of Criminal Procedure of Ukraine, with observance of human rights and freedoms (although associated with their restriction) and are aimed at obtaining factual data about the circumstances that are subject to proof and are significant for criminal proceedings, the reliability or unreliability, the possibility or impossibility of using other evidence. It has been emphasized that an important task in criminal proceedings is to ensure due legal procedure and prevent violations of the rights, freedoms and legitimate interests of participants in criminal proceedings during procedural actions related to the restriction of the rights and freedoms of a person, including secret investigative (search) actions. It has been stated that, taking into account the interdisciplinary nature of covert investigative (search) actions, due to the combination of secret methods and forms of their conduct, inherent in operational-search measures, with the scope of their application – criminal proceedings (criminal procedural activities), in practice, unfortunately, there are incorrect interpretations and, as a result, the application of the norms of current legislation. It has been emphasized that in order to correct the situation, as well as further streamline both scientific provisions and practical recommendations regarding the application of the norms of criminal procedural law, which regulate the procedure for conducting covert investigative (search) actions and the use of their materials in criminal proceedings, it is worth regularly reviewing the relevant judicial practice. It has been found out that today the legal positions of the Supreme Court have been formed regarding: the presence of grounds for conducting a covert investigative (search) action; the presence of the authority of a person to conduct a covert investigative (search) action; compliance with the procedure for recording the progress and results of covert investigative (detective) actions; the possibility of using the results of covert investigative (detective) actions for evidence, other purposes, or to transfer information; distinguishing provocation of a crime from permissible behavior of law enforcement agencies; etc.
Keywords: covert investigative (search) actions; evidence; means of proof; criminal proceedings; criminal procedural legislation; procedural order; legal positions; case law; due process